2022
DOI: 10.1088/1361-6633/ac97a8
|View full text |Cite
|
Sign up to set email alerts
|

Scaling infrared detectors—status and outlook

Abstract: The predicted “Law 19” benchmark for HgCdTe photodiode performance established in 2019 is a milestone in the development of infrared detectors and make the dream of Elliott and colleagues, who in 1999 wrote that there is no fundamental obstacle to obtaining room temperature operation of photon detectors at room temperature with background-limited performance even in reduced fields of view [C.T. Elliott et al., Appl. Phys. Lett. 74(9), 2881 (1999)]. This circumstance will make it possible to achieve in the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 124 publications
0
23
0
Order By: Relevance
“…As a critical component in the THz field, the challenge of efficient photodetection and fast response remains [ 7 ]. Currently, several commercial detectors are available, including GaN detectors, GaAs-based detectors, and thermal detectors, yet their response times being in the millisecond range limits their application in the field of THz technology [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a critical component in the THz field, the challenge of efficient photodetection and fast response remains [ 7 ]. Currently, several commercial detectors are available, including GaN detectors, GaAs-based detectors, and thermal detectors, yet their response times being in the millisecond range limits their application in the field of THz technology [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the trend of cooled thermal imager technologies, uncooled thermal imagers also aim for smaller pixel pitches to enable higher optical resolutions. [4][5][6] In consequence, this trend led to the development of uncooled thermal imagers based on microbolometers demonstrating their electro-optical functionality down to pixel sizes of only 6 µm in case of Fraunhofer IMS's scalable nanotube-microbolometer technology [1][2][3] and in parallel, to further uncooled thermal imagers with pixel pitches below 10 µm manufactured by InfiRay 7 and Lynred 8 . Since the detector size of those microbolometers continously approaches the optical detection limit in the long wavelength infrared (LWIR), 9 it seems to be only a matter of time when this physical limit will finally be reached.…”
Section: Introductionmentioning
confidence: 99%
“…are too various BM design and fabrication considerations. Further details of these fabrication techniques can be found in the recent review articles and book chapter; readers are strongly suggested to refer them for a more comprehensive understanding.…”
mentioning
confidence: 99%